Recondition Cylinder Head Engine Wartsila Diesel 18V32DF - Hendri Van Hoten; Hairul Gustriranda; Nurbaiti Nurbaiti (Department of Mechanical Engineering, Universitas Andalas, 2020)
Power House Division (PHD) is one of the divisions that is part of PT. ABC. As an electrical energy supplier in XYZ area, Power House Division consist of four Power House, which each Power House has several engine. The first Power House (PH 1) consist of two Diesel engine Generator (DG) and one Gas Turbine in the second Power House. The third and fourth Power House consist of seven Diesel engine Generator.To keep the engine performance stable that is produce maximum power and prevent unknown damage that it make engine trip then the overhaul activity done. overhaul activity is carried out the process of replacement and recondition of spare parts of all parts of the engine. The recondition process is done in the cylinder head.Cylinder Head is an important component of a machine function as a combustion place and as an inlet and airway. There are long stages done In the process of recondition cylinder head from the demolition of cylinder head components to the re-installation of these components. There is a cylinder head that has crack, so it can not be recondition. It should be replaced with a new cylinder head. The machining process is used recondition cylinder head. They are Cutting, Lapping, and Grinding. In the pocket cylinder head, the recondition is found that it has a rust so that the size of the pocket and oversize that it has sticks around the pocket. Grinding process performed on uneven parts of valve.